Pharmacists' impact on quality and financial metrics utilizing virtual care platforms during the coronavirus pandemic. (8th February 2022) - Glovacz, Joseph W; Betts, Sarah G; Cross, Steven; Powell, Justin
Abstract: Purpose: Because of rising concern about coronavirus disease 2019 transmission, there has been a large shift from face-to-face, in-office visits to a virtual care model. The purpose of this article is to explain how Ascension Florida Gulf Coast was able to maximize the utility of ambulatory care pharmacists (ACPs) in the primary care setting during the pandemic and to provide guidance for creating a sustainable billing and practice model in the event of another global health crisis. Summary: By employing telehealth services, our ACPs were able to continue to co-manage chronic disease states for documented diagnoses while still maintaining health-system revenue in the midst of a global health crisis. Utilizing various virtual platforms, ACPs were able to accommodate the needs of our patients while addressing concerns related to the compatibility and user friendliness of the platforms for our diverse patient population. ACPs used traditional incident-to evaluation and management services current procedural terminology billing codes with a virtual visit modifier for billing and tracking purposes. Conclusion: Utilizing various virtual care platforms, our ACPs completed 447 patient encounters within the first 7 months of the pandemic. During this time, our ACPs addressed various population health metrics, specifically for patients diagnosed with diabetes without an active claim for a cholesterol-lowering medication, in addition to performing chronic disease management. Our ACPs had a 23% success rate for statin initiation in patients reviewed and contacted. By adopting virtual care options, our ACPs were able to effectively co-manage and educate patients while improving quality metrics and generating 50, 662.24 in billable encounters for the health system during a global health crisis. The addition of ACP virtual encounters to primary care clinics both increases access to healthcare and improves patient care quality and outcomes while limiting revenue losses in our local health system.